Proximal contact areas of maxillary anterior teeth and their influence on interdental papilla - Abhay P. Kolte; Rajashri A. Kolte; Pranjali Bawankar (Saudi Dental Journal)
Objectives: Open gingival embrasures leading to appearance of black triangles which apart from being unesthetic contribute towards food retention, adversely affecting the health of the periodontium. Correction of such papillary deformities is extremely challenging, which requires an in depth knowledge about the interproximal geometry for the appropriate management of interdental papilla. So, the present study was aimed to determine the proximal contact areas of maxillary anterior teeth and their influence on the interdental papilla. Materials and methods: In 200 periodontally healthy patients equally divided into 21–40 years (Group I) and 41–60 years (Group II) of age group amounting to a total of 1400 interdental papillae in maxillary anterior teeth were examined to compute the apicocoronal Proximal contact area (PCA), Proximal contact area proportion (PCAP), and dimensions between alveolar crest and apical contact point (D1) to assess their influence on presence or absence of interdental papilla. Results: The PCA dimensions were maximum for Central incisor-Central incisor measuring about 3.90 ± 0.93 mm and 3.97 ± 0.90 mm for Group I males and females respectively and 3.86 ± 1.22 mm and 3.63 ± 1.14 mm for males and female patients in Group II respectively. There was a gradual reduction till Canine-Premolar. Similar trend was followed in PCAP and D1. Consistently more dimensions of D1 were observed in Group II as compared to Group I which influenced the presence of papilla which was predominantly found in Group I patients amongst both the sexes. Conclusion: There was a gradual decrease in the PCA and PCAP in the distal direction anteroposteriorly from maxillary central incisors to first premolars on either sides. The younger age group of both the sexes exhibit greater presence of interdental papilla owing to the lesser D1 dimensions as compared to the older patients. Keywords: Interdental papilla, Proximal contact, Esthetic